Endothelin-1 promotes vascular smooth muscle cell migration across the artery wall: a mechanism contributing to vascular remodelling and intimal hyperplasia in giant-cell arteritis. Issue 9 (12th June 2017) - Planas-Rigol, Ester; Terrades-Garcia, Nekane; Corbera-Bellalta, Marc; Lozano, Ester; Alba, Marco A; Segarra, Marta; Espígol-Frigolé, Georgina; Prieto-González, Sergio; Hernández-Rodríguez, José; Preciado, Sara; Lavilla, Rodolfo; Cid, Maria C
Abstract : Background: Giant-cell arteritis (GCA) is an inflammatory disease of large/medium-sized arteries, frequently involving the temporal arteries (TA). Inflammation-induced vascular remodelling leads to vaso-occlusive events. Circulating endothelin-1 (ET-1) is increased in patients with GCA with ischaemic complications suggesting a role for ET-1 in vascular occlusion beyond its vasoactive function. Objective: To investigate whether ET-1 induces a migratory myofibroblastic phenotype in human TA-derived vascular smooth muscle cells (VSMC) leading to intimal hyperplasia and vascular occlusion in GCA. Methods and results: Immunofluorescence/confocal microscopy showed increased ET-1 expression in GCA lesions compared with control arteries. In inflamed arteries, ET-1 was predominantly expressed by infiltrating mononuclear cells whereas ET receptors, particularly ET-1 receptor B (ETB R), were expressed by both mononuclear cells and VSMC. ET-1 increased TA-derived VSMC migration in vitro and α-smooth muscle actin (αSMA) expression and migration from the media to the intima in cultured TA explants. ET-1 promoted VSMC motility by increasing activation of focal adhesion kinase (FAK), a crucial molecule in the turnover of focal adhesions during cell migration. FAK activation resulted in Y397 autophosphorylation creating binding sites for Src kinases and the p85 subunit of PI3kinases which, upon ET-1 exposure, colocalised with FAK at the focal adhesions of migrating VSMC. Accordingly, FAK or PI3K inhibition abrogated ET-1-induced migration in vitro. Consistently, ET-1 receptor A and ETB R antagonists reduced αSMA expression and delayed VSMC outgrowth from cultured GCA-involved artery explants. Conclusions: ET-1 is upregulated in GCA lesions and, by promoting VSMC migration towards the intimal layer, may contribute to intimal hyperplasia and vascular occlusion in GCA.